Interpersonal stress generation among young adolescents: vulnerable and resilient interpersonal behaviors and the generation of negative and positive interpersonal events - Kuroda, Yuji (Frontiers in Psychology, 2023)
Background Theoretical and empirical studies on stress generation suggest four event generation processes: (1) vulnerability factors predict more negative interpersonal events; (2) vulnerability factors predict fewer positive interpersonal events; (3) resiliency factors predict fewer negative interpersonal events; and (4) resiliency factors predict more positive interpersonal events. However, few studies have examined these four processes simultaneously within a single analytic model. Therefore, it is unclear whether vulnerability and resiliency factors make unique and differential contributions to the occurrences of negative and positive interpersonal events. General objectives This study aimed to fill this important gap by examining whether social withdrawal and excessive reassurance-seeking (vulnerable interpersonal behaviors) and prosocial behaviors (a resilient interpersonal behavior) uniquely and differentially predict the occurrences of negative and positive peer events among young adolescents. This study also examined the sex differences in these relationships. Methods One hundred and ninety-eight students (109 girls) were recruited from a public middle school in Japan. A multiple-group path analysis was conducted to examine possible sex differences. Results Social withdrawal uniquely predicted more negative peer events for boys and fewer positive peer events for boys and girls. Excessive reassurance-seeking uniquely predicted both more negative peer events and more positive peer events for boys and girls. Prosocial behavior uniquely predicted more positive peer events for boys and girls. Conclusion This study underscores the unique and differential roles of vulnerable and resilient interpersonal behaviors in predicting negative and positive peer events among young adolescents. These findings not only advance our understanding of stress generation processes but also have broader implications for adolescent development and well-being.